2005
DOI: 10.1016/j.ijfoodmicro.2004.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Survival curves of heated bacterial spores: effect of environmental factors on Weibull parameters

Abstract: The classical D-value of first order inactivation kinetic is not suitable for quantifying bacterial heat resistance for non-log linear survival curves. One simple model derived from the Weibull cumulative function describes non-log linear kinetics of micro-organisms. The influences of environmental factors on Weibull model parameters, shape parameter "p" and scale parameter "delta", were studied. This paper points out structural correlation between these two parameters. The environmental heating and recovery c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 27 publications
3
65
1
2
Order By: Relevance
“…Results showed that the p parameter associated to the shape of survival curves was dependent from the type of preculture as it was supposed by Couvert et al (2005). Concave upward survival curves were observed for all kinetics and attested by a p value superior to one.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Results showed that the p parameter associated to the shape of survival curves was dependent from the type of preculture as it was supposed by Couvert et al (2005). Concave upward survival curves were observed for all kinetics and attested by a p value superior to one.…”
Section: Resultsmentioning
confidence: 64%
“…This equation was used by different authors (Mafart et al, 2002;Virto et al, 2005;Carlin et al, 2006;Buzrul, 2007) and was implemented in this work as primary model. The shape parameter p variation on the goodness of fit of models was shown by Couvert et al (2005) to have slight influence so that a single pvalue can be used for a given microbial population (same physiological state, same preculture) (Couvert et al, 2005). A single overall estimation of p-value per strain was determined, regardless of environmental conditions (water type) and recovery (medium used for colony counting), as it seemed to be enough for bacterial food predictive modelling and canning process calculation (Mafart et al, 2002 …”
Section: Campylobacter Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some common models, like Bigelow or Mafart models (Couvert, Gaillard, Savy, Mafart, & Leguerinel, 2005) were described. In tutorials, students could evaluate which parameter had the highest impact on the logarithmic destruction of a microbial population when several factors varied together.…”
Section: Ijfs October 2015 Volume 4 Pages 134-140mentioning
confidence: 99%
“…Podobnie Couvert i wsp. [1] twierdzą, że w przypadku nieliniowego przebiegu krzywej przeżycia spor, odczytywanie wartości D z odcinka przebiegającego według reakcji I rzędu do określenia ciepłooporności mikroorganizmów jest nieodpowiednie i obarczone dużym błędem.…”
Section: Wprowadzenieunclassified